Anti-inflammatory and remyelinating effects of fexagratinib in experimental multiple sclerosis - Gurski, Fynn; Shirvanchi, Kian; Rajendran, Vinothkumar; Rajendran, Ranjithkumar; Megalofonou, Fevronia-Foivi; Böttiger, Gregor; Stadelmann, Christine; Bhushan, Sudhanshu; Ergün, Süleyman; Karnati, Srikanth; Berghoff, Martin; Justus Liebig University Giessen (My University, 2025)
Background and Purpose: FGF, VEGFR-2 and CSF1R signalling pathways play a key role in the pathogenesis of multiple sclerosis (MS). Selective inhibition of FGFR by infigratinib in MOG35-55-induced experimental autoimmune encephalomyelitis (EAE) prevented severe first clinical episodes by 40%; inflammation and neurodegeneration were reduced, and remyelination was enhanced. Multi-kinase inhibition of FGFR1-3, CSFR and VEGFR-2 by fexagratinib (formerly known as AZD4547) may be more efficient in reducing inflammation, neurodegeneration and regeneration in the disease model. Experimental Approach: Female C57BL/6J mice were treated with fexagratinib (6.25 or 12.5 mg·kg−1) orally or placebo over 10 days either from time of EAE induction (prevention experiment) or onset of symptoms (suppression experiment). Effects on inflammation, neurodegeneration and remyelination were assessed at the peak of the disease (Day 18/20 post immunization) and the chronic phase of EAE (Day 41/42). Key Results: In the prevention experiment, treatment with 6.25 or 12.5 mg·kg−1 fexagratinib prevented severe first clinical episodes by 66.7% or 84.6% respectively. Mice treated with 12.5 mg·kg−1 fexagratinib hardly showed any symptoms in the chronic phase of EAE. In the suppression experiment, fexagratinib resulted in a long-lasting reduction of severe symptoms by 91 or 100%. Inflammation and demyelination were reduced, and axonal density, numbers of oligodendrocytes and their precursor cells, and remyelinated axons were increased by both experimental approaches. Conclusion and Implications: Multi-kinase inhibition by fexagratinib in a well-tolerated dose of 1 mg·kg−1 in humans may be a promising approach to reduce inflammation and neurodegeneration, to slow down disease progression and support remyelination in patients.
Keywords: ddc:610